Effects of chronic heat exposure on growth performance, intestinal epithelial histology, appetite‐related hormones and genes expression in broilers. (3rd April 2018) - He, Xiaofang; Lu, Zhuang; Ma, Bingbing; Zhang, Lin; Li, Jiaolong; Jiang, Yun; Zhou, Guanghong; Gao, Feng
Abstract: BACKGROUND: Heat stress often occurs in the modern poultry industry, which impairs growth performance, particularly via reducing appetite. This study was aimed to investigate the mechanism of attenuating appetite by chronic heat exposure in broilers. A total of 144 broilers (28 days old) were allocated to normal control (NC, 22 °C), heat stress (32 °C), and pair‐fed (22 °C) groups. RESULTS: Chronic heat exposure significantly increased cloacal temperatures and respiration rates, decreased the average daily feed intake and average daily gain, increased feed‐to‐gain ratio compared with the NC group, and elevated the concentrations of ghrelin and cholecystokinin (CCK) both in serum and intestine, as well as peptide YY and somatostatin in intestine on 35‐ or 42‐day‐old broilers. Moreover, heat exposure decreased villi height (VH) and the ratio of VH to crypt depth (CD), while it increased CD in the jejunum on 35‐ and 42 day‐olds, increased ( P < 0.05) the concentrations of valine and isoleucine in plasma on 42 days, and upregulated ( P < 0.05) the expression of taste receptor type 1 members 1 and 3 ( T1R1 and T1R3 ), CCK, and ghrelin in the intestine on 35‐ or 42‐day‐old broilers. CONCLUSION: Chronic heat exposure impairs the performance, intestinal morphology and appetite, which may be correlated with the increased secretion or gene expression of appetite‐related hormones and genes, and the higher expression of nutrient‐sensing receptors (T1R1 and T1R3) in broilers. © 2018 Society of Chemical Industry